The role of levosimendan in acute heart failure complicating acute coronary syndrome: A review and expert consensus opinion. (1st September 2016) - Nieminen, Markku S.; Buerke, Michael; Cohen-Solál, Alain; Costa, Susana; Édes, István; Erlikh, Alexey; Franco, Fatima; Gibson, Charles; Gorjup, Vojka; Guarracino, Fabio; Gustafsson, Finn; Harjola, Veli-Pekka; et al.
Abstract: Acute heart failure and/or cardiogenic shock are frequently triggered by ischemic coronary events. Yet, there is a paucity of randomized data on the management of patients with heart failure complicating acute coronary syndrome, as acute coronary syndrome and cardiogenic shock have frequently been defined as exclusion criteria in trials and registries. As a consequence, guideline recommendations are mostly driven by observational studies, even though these patients have a particularly poor prognosis compared to heart failure patients without signs of coronary artery disease. In acute heart failure, and especially in cardiogenic shock related to ischemic conditions, vasopressors and inotropes are used. However, both pathophysiological considerations and available clinical data suggest that these treatments may have disadvantageous effects. The inodilator levosimendan offers potential benefits due to a range of distinct effects including positive inotropy, restoration of ventriculo-arterial coupling, increases in tissue perfusion, and anti-stunning and anti-inflammatory effects. In clinical trials levosimendan improves symptoms, cardiac function, hemodynamics, and end-organ function. Adverse effects are generally less common than with other inotropic and vasoactive therapies, with the notable exception of hypotension. The decision to use levosimendan, in terms of timing and dosing, is influenced by the presence of pulmonary congestion, and blood pressure measurements. Levosimendan should be preferred over adrenergic inotropes as a first line therapy for all ACS-AHF patients who are under beta-blockade and/or when urinary output is insufficient after diuretics. Levosimendan can be used alone or in combination with other inotropic or vasopressor agents, but requires monitoring due to the risk of hypotension. Highlights: Heart failure/cardiogenic shock is frequently triggered by ischemic coronary events. Levosimendan was shown to improve hemodynamics compared to other inotropes or IABP. The recommendation to use levosimendan varies depending on the blood pressure values. Levosimendan should be used when urinary output is insufficient after diuretics. Levosimendan should be preferred over adrenergic inotropes in patients with beta-blockers.